Optimization of growth of oyster mushroom mycelium (Pleurotus sp.) from Tasikmalaya on several kinds of cereal medium - Khusnul Khusnul (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2019)
Pleurotus sp. or oyster mushroom is one type of edible mushroom that contains essential nutrients for the human body. This mushroom has been widely cultivated in Indonesia, one of which is Pleurotus sp. from Tasikmalaya. The key to the success of oyster mushroom cultivation is the seeds and growing medium or baglog, while the factors that influence the quality of the seeds include the type of medium. This study aims to determine 1) the effect of the type of seed medium from the type of cereals used on the growth of mycelium Pleurotus sp. from Tasikmalaya, 2) determine the type of seed medium that has the best mycelium growth. This study uses an experimental method with a Completely Randomized Design (CRD). The parameters measured include the main parameters, namely the rate of growth of mycelium Pleurotus sp. from Tasikmalaya on the seed medium. Supporting parameters are the quality of mycelium growth in the seed medium, the proximate value of cereals used for the seed medium. The results of the analysis showed that the medium of cereals used as seeds ready for cultivation could affect the quality of the seeds produced. The seedling medium from milled corn has the best growth of mycelium.